Extracellular Vesicles From Epicardial Fat Facilitate Atrial Fibrillation. Issue 25 (1st April 2021) - Shaihov-Teper, Olga; Ram, Eilon; Ballan, Nimer; Brzezinski, Rafael Y.; Naftali-Shani, Nili; Masoud, Rula; Ziv, Tamar; Lewis, Nir; Schary, Yeshai; Levin-Kotler, La-Paz; Volvovitch, David; Zuroff, Elchanan M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The role of epicardial fat (eFat)-derived extracellular vesicles (EVs) in the pathogenesis of atrial fibrillation (AF) has never been studied. We tested the hypothesis that eFat-EVs transmit proinflammatory, profibrotic, and proarrhythmic molecules that induce atrial myopathy and fibrillation. Methods: We collected eFat specimens from patients with (n=32) and without AF (n=30) during elective heart surgery. eFat samples were grown as organ cultures, and the culture medium was collected every 2 days. We then isolated and purified eFat-EVs from the culture medium, and analyzed the EV number, size, morphology, specific markers, encapsulated cytokines, proteome, and microRNAs. Next, we evaluated the biological effects of unpurified and purified EVs on atrial mesenchymal stromal cells and endothelial cells in vitro. To establish a causal association between eFat-EVs and vulnerability to AF, we modeled AF in vitro using induced pluripotent stem cell–derived cardiomyocytes. Results: Microscopic examination revealed excessive inflammation, fibrosis, and apoptosis in fresh and cultured eFat tissues. Cultured explants from patients with AF secreted more EVs and harbored greater amounts of proinflammatory and profibrotic cytokines, and profibrotic microRNA, as well, than those without AF. The proteomic analysis confirmed the distinctive profile of purified eFat-EVs from patients with AF. In vitro, purified and unpurified eFat-EVs from patients with AF had a greater effect on proliferation and migration of human mesenchymal stromal cells and endothelial cells, compared with eFat-EVs from patients without AF. Last, whereas eFat-EVs from patients with and without AF shortened the action potential duration of induced pluripotent stem cell–derived cardiomyocytes, only eFat-EVs from patients with AF induced sustained reentry (rotor) in induced pluripotent stem cell–derived cardiomyocytes. Conclusions: We show, for the first time, a distinctive proinflammatory, profibrotic, and proarrhythmic signature of eFat-EVs from patients with AF. Our findings uncover another pathway by which eFat promotes the development of atrial myopathy and fibrillation.